Tetrasomy 15Q11-Q13 identified by fluorescence in situ hybridization in a patient with autistic disorder - Silva, Ana Elizabete [UNESP]; Vayego-Lourenço, Sheila Adami; Fett-Conte, Agnes Cristina; Goloni-Bertollo, Eny Maria; Varella-Garcia, Marileila (FapUNIFESP (SciELO), 2002)
We report a female child with tetrasomy of the 15q11-q13 chromosomal region, and autistic disorder associated with mental retardation, developmental problems and behavioral disorders. Combining classical and molecular cytogenetic approaches by fluorescence in situ hybridization technique, the karyotype was demonstrated as 47,XX,+mar.ish der(15)(D15Z1++,D15S11++,GABRB3++,PML-). Duplication of the 15q proximal segment represents the most consistent chromosomal abnormality reported in association with autism. The contribution of the GABA receptor subunit genes, and other genes mapped to this region, to the clinical symptoms of the disease is discussed.
Keywords: 15q11-q13; Autism; Fluorescence in situ hybridization; GABA receptors; Tetrasomy 15; 4 aminobutyric acid receptor; adolescent; aneuploidy; autism; case report; chromosome 11; chromosome 13; chromosome 15; female; fluorescence in situ hybridization; genetics; human; human chromosome; karyotyping; Adolescent; Aneuploidy; Autistic Disorder; Chromosomes, Human; Chromosomes, Human, Pair 11; Chromosomes, Human, Pair 13; Chromosomes, Human, Pair 15; Female; Humans; In Situ Hybridization, Fluorescence; Karyotyping; Receptors, GABA